"As Reliable as a Kalashnikov Rifle": How Sputnik News Promotes Russian Vaccine Technologies in the Turkish Twittersphere. (February 2023) - Furman, Ivo Ozan; Gürel, Kurt Bilgin; Sivaslıoğlu, Fırat Berk
Established in 2014, SputnikTR (a localized version of Sputnik News) is the most popular pro-Russian media outlet active in Turkey. The news content published by SputnikTR's Twitter account currently attracts the highest engagement rates among the international public broadcasters active in Turkey. SputnikTR's official Twitter account has more followers (1M) than Sputnik News English (326K). This article argues that SputnikTR's Twitter account is used to promote Russian vaccine technologies in Turkey. We believe that it is also a conduit for the dissemination of pro-Russian as well as anti-Western narratives to the Turkish online public. Using a computational methodology, we collected 2, 782 vaccine-related tweets posted by SputnikTR's Twitter account between April 2019 and April 2021. We deployed framing as well as critical discourse analysis to study the contents of our dataset. Our findings suggest that SputnikTR uses (a) disinformation as well as misinformation in vaccine-related news and (b) unethical communication techniques to maximize engagement with content posted on Twitter. Our findings are significant insofar as they are the first documented instances of Russian propaganda efforts on Turkish Twitter. These efforts seem to be focused on promoting the Russian vaccine while encouraging public hesitancy toward Western vaccine technologies.